2017
DOI: 10.1177/2040620717719851
|View full text |Cite
|
Sign up to set email alerts
|

Radotinib and its clinical potential in chronic-phase chronic myeloid leukemia patients: an update

Abstract: Abstract:Although imatinib has dramatically improved major outcomes in patients with chronic myeloid leukemia (CML), there are newer tyrosine kinase inhibitors (TKIs) approved worldwide for the treatment of resistant cases, and two second-generation TKIs (dasatinib, nilotinib) are approved in some nations for treating patients in the upfront setting. Radotinib (IY5511HCL, Supect®) is a novel and selective second-generation BCR-ABL1 TKI, which is currently approved in Korea for the treatment of patients with CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Nilotinib is resistant to Y253H/F, E255K/V, and T315I [ 27 , 34 , 35 , 93 ] but is an alternative for second line treatment in cases of other mutations. Very similar to Nilotinib, the Korean approved TKI (Radotinib) presented an in vitro IC 50 of 34 nM [ 41 , 239 ]. Nevertheless, cases of Radotinib resistance have been associated with BCR-ABL1 point mutations, namely Y235H, E255V, T315I, and T315M [ 239 ] ( Table 1 ).…”
Section: Therapeutic Approaches Against Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Nilotinib is resistant to Y253H/F, E255K/V, and T315I [ 27 , 34 , 35 , 93 ] but is an alternative for second line treatment in cases of other mutations. Very similar to Nilotinib, the Korean approved TKI (Radotinib) presented an in vitro IC 50 of 34 nM [ 41 , 239 ]. Nevertheless, cases of Radotinib resistance have been associated with BCR-ABL1 point mutations, namely Y235H, E255V, T315I, and T315M [ 239 ] ( Table 1 ).…”
Section: Therapeutic Approaches Against Resistancementioning
confidence: 99%
“…Very similar to Nilotinib, the Korean approved TKI (Radotinib) presented an in vitro IC 50 of 34 nM [ 41 , 239 ]. Nevertheless, cases of Radotinib resistance have been associated with BCR-ABL1 point mutations, namely Y235H, E255V, T315I, and T315M [ 239 ] ( Table 1 ). Bosutinib, a second-generation TKI, is a dual SRC/ABL1 kinase inhibitor that binds to BCR-ABL1 in both conformations, as described for Dasatinib [ 240 , 241 ].…”
Section: Therapeutic Approaches Against Resistancementioning
confidence: 99%
“…This follows the data from the BFORE trial published in 2018 that compares bosutinib to imatinib in newly diagnosed CML-CP patients [10,11]. The panel recognized radotinib [12] and its randomized comparison with imatinib in Korea [13] but, concluded that further information is needed for this drug before its universal recommendation for treatment. Asciminib is mentioned as a potential future treatment option.…”
Section: Newer Tkis and Other Treatmentsmentioning
confidence: 71%
“…[13][14][15] Radotinib is approved in South Korea as a secondline treatment for chronic phase chronic myeloid leukemia (CML-CP). 16,17 It inhibits the tyrosine kinase BCR-ABL and platelet-derived growth factor receptor. 16,18 Recently, Phase III clinical trial on the efficacy and safety of radotinib demonstrated its superiority over imatinib in generating complete cytogenetic response and major molecular response in patients newly evaluated with Philadelphia chromosomepositive CML-CP.…”
Section: Introductionmentioning
confidence: 99%